THE EFFECTIVENESS OF PICTURE SERIES IN TEACHING WRITING NARRATIVE TEXT OF THE FIRST GRADE AT SMAN 1 PADEMAWU - Setiyawan, Arisandi (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
The use of picture in the teaching and learning process is very important. The students can understand easily what is happening in the pictures as they provide material that offer guidance on vocabulary, sentence structure, and organization yet let the students write about new subject matter. Meanwhile, there are four skills in learning English and writing skill may be considered as the most difficult of the language skills. The objective of this research is to investigate the effectiveness of picture series in writing skill, particularly writing narrative text at SMAN 1 Pademawu. The population of the research was the first-grade students. The research methodology was an experimental research, which was conducted in two groups. Grade X-IPS 1 as the experimental group and grade X-IPS 2 as the control group. The researcher gave writing test (pre-test and post-test) to gather the data. Meanwhile, the data was analyzed using SPSS V.21. The result showed that there was a significant difference between the English writing skill of students taught by using picture series and those who were not taught by using picture series. It can be proved by the result of t-observation was 0,01<0,05 with the significant level was 0,05. It means that Ha which states that there is significant effect of picture series in teaching writing narrative text is accepted. Meanwhile, Ho which states that there is no significant effect of picture series in teaching writing narrative text is rejected. In other word, it can be concluded that picture series is effective to teach English especially for writing narrative text of the first grade at SMAN 1 Pademawu.